The Relationship between Capital Financial, Accounting Capability and Micro-, Small- and Medium-Sized Enterprises' (MSMEs) Financial Performance in Indonesia - Winarsih, Winarsih; Winarti, Wiwin; Machmuddah, Zaky; Tahar, Emiza binti (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
This study examines the role of financial capital in mediating the relationship between accounting capability and Micro-, Small- and Medium-Sized Enterprises' (MSME) financial performance. Using Yamane formula, the samples are 407 MSMEs in Central Java Province. Data was collected from questionnaires that distributed to and filled by owners of the sample MSME. WarpPLS was used to analyased the research data. This study found that accounting capability and financial capital have a positive influence on financial performance. Financial capital mediates the relationship between accounting capability and financial performance. Thus, this study confirms the importance of accounting capability to increase financial capital and financial performace of MSME.